2007
DOI: 10.1037/1089-2699.11.2.79
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Dimensions of Diversity: Cross-Categorization and the Functioning of Diverse Work Groups.

Abstract: AND KEYWORDS AbstractWe conducted an experiment to show how the interplay between informational diversity and other dimensions of diversity can account for some of the inconsistent effects of informational

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 77 publications
7
97
1
2
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 12 Several studies supported aspects of the CEM, such as the centrality of elaboration processes for the positive consequences of diversity (e.g., Homan et al, 2007a;Homan, van Knippenberg, van Kleef, & De Dreu, 2007b), the moderating effects of trait operationalizations of identity threat such as pro-diversity beliefs and openness (e.g., Hentschel, Shemla, Wegge, & Kearney, 2013;Homan et al, 2008;Homan et al, 2007a;Nakui, Paulus, & van Oudenhoven-van der Zee, 2011; van Dick, van Knippenberg, Hagele, Guillaume, & Brodbeck, 2008;Whitt, Edison, Pascarella, Terenzini, & Nora, 2001), and the moderating role of task motivation (Meyer & Schermuly, 2012). Further moderators that go beyond those explicitly mentioned in the CEM include certain leadership styles (Homan & Greer, 2013;, team members' need for cognition (Kearney, Gebert, & Voelpel, 2009), norms (Mitchell & Boyle, 2015, and leader inclusiveness , to name only a few.…”
Section: The Team-level Compositional Approach To Team Diversitymentioning
confidence: 98%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 12 Several studies supported aspects of the CEM, such as the centrality of elaboration processes for the positive consequences of diversity (e.g., Homan et al, 2007a;Homan, van Knippenberg, van Kleef, & De Dreu, 2007b), the moderating effects of trait operationalizations of identity threat such as pro-diversity beliefs and openness (e.g., Hentschel, Shemla, Wegge, & Kearney, 2013;Homan et al, 2008;Homan et al, 2007a;Nakui, Paulus, & van Oudenhoven-van der Zee, 2011; van Dick, van Knippenberg, Hagele, Guillaume, & Brodbeck, 2008;Whitt, Edison, Pascarella, Terenzini, & Nora, 2001), and the moderating role of task motivation (Meyer & Schermuly, 2012). Further moderators that go beyond those explicitly mentioned in the CEM include certain leadership styles (Homan & Greer, 2013;, team members' need for cognition (Kearney, Gebert, & Voelpel, 2009), norms (Mitchell & Boyle, 2015, and leader inclusiveness , to name only a few.…”
Section: The Team-level Compositional Approach To Team Diversitymentioning
confidence: 98%
“…Migdal et al's analysis further showed that intergroup bias is reduced when diversity attributes are crossed, which reduces intragroup conflict and enhances information elaboration (Homan et al, 2007b). Finally, Marcus-Newhall, Miller, Holtz, and Brewer (1993) showed that crossing existing subgroups with role expectancies decreased intergroup bias compared to converging subgroups with roles.…”
Section: Salience Of Intra-group Differencesmentioning
confidence: 99%
“…Under these conditions, teams may suffer from the detrimental effects of diversity. Gaertner et al (1989) found that when subgroups were made salient by rewarding teams based on subgroup performance, inter-subgroup processes deteriorated (see also Homan et al, 2007b). Similarly, Lau and Murnighan (2005) showed that convergence of multiple diversity characteristics-in their study ethnicity and sex-increased the salience of subgroups, resulting in deteriorated group functioning.…”
Section: Salience Of Intra-group Differencesmentioning
confidence: 99%
See 2 more Smart Citations